Acute medicine : a practical guide to the management of medical emergencies - Sprigings, David; Chambers, John; Sprigings, David (Wiley Blackwell, 2018)
"Acute Medicine offers an accessible and concise guide to the practical management of all acute medical problems likely to be encountered in the emergency department, ambulatory care centre, acute medical unit or on the wards. Reflecting the maturation of acute medicine as a separate specialty, the book is divided into common presentations, specific problems and procedures. New to the fifth edition is a chapter on bed-side ultrasonography; throughout, emphasis is placed on patient safety, and the use of flow diagrams, tables and figures ensures that key information is quickly accessible. Thoroughly revised by experts in the subject, and updated to reflect current approaches to diagnosis and management, Acute Medicine is an excellent companion for the trainee as well as an aide-mmoire for the more experienced physician"- Resumé vydavatel
Preceded by Acute medicine / David Sprigings, John Chambers. 4th ed. 2008.
Keywords: urgentní medicína -- metody; lékařská služba první pomoci; emergency medicine -- methods; emergency medical service; elektronické knihy; příručky; electronic books; handbooks and manuals